2009
DOI: 10.1103/physrevlett.102.208301
|View full text |Cite
|
Sign up to set email alerts
|

Manipulation of Colloids by a Nonequilibrium Depletion Force in a Temperature Gradient

Abstract: The non-equilibrium distribution of colloids in a polymer solution under a temperature gradient is studied experimentally. A slight increase of local temperature by a focused laser drives the colloids towards the hot region, resulting in the trapping of the colloids irrespective of their own thermophoretic properties. An amplification of the trapped colloid density with the polymer concentration is measured, and is quantitatively explained by hydrodynamic theory. The origin of the attraction is a migration of … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

13
275
1
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 229 publications
(290 citation statements)
references
References 27 publications
13
275
1
1
Order By: Relevance
“…The strength of the orientation observed using the present model may appear small. However, it is of the same order as the orientation observed in polar fluids under temperature gradients, which results in significant electrostatic fields, ∼ 10 4 − 10 6 V/m for thermal gradients, 10 6 − 10 8 K/m, which are achievable in experimental set ups [5,22]. Interestingly, the orientation is also similar in magnitude to that observed in water at the liquid-water interface [23].…”
mentioning
confidence: 56%
See 1 more Smart Citation
“…The strength of the orientation observed using the present model may appear small. However, it is of the same order as the orientation observed in polar fluids under temperature gradients, which results in significant electrostatic fields, ∼ 10 4 − 10 6 V/m for thermal gradients, 10 6 − 10 8 K/m, which are achievable in experimental set ups [5,22]. Interestingly, the orientation is also similar in magnitude to that observed in water at the liquid-water interface [23].…”
mentioning
confidence: 56%
“…We show that the preferred orientation of the molecules follows the same trends observed in the Soret effect of binary mixtures. We argue this is a general effect that should be observed in a wide range of length scales.Thermal gradients are responsible for a wide range of non equilibrium effects, electron transport (thermoelectricity) [1], mass transport in suspensions (thermophoresis) [2][3][4][5][6], mass separation in liquid mixtures [7][8][9] and nucleation and growth of colloidal crystals [10]. Recently it has been shown that temperature gradients can induce orientation in polar fluids, a physical effect that is supported by Non Equilibrium Thermodynamics Theory (NET) and that can be explained in terms of the coupling of a polarization field and a temperature gradient [11].…”
mentioning
confidence: 99%
“…[20,30,31] the temperature gradient is perpendicular to the boundary as in Fig. 1; a parallel configuration is used in [32,33], with the particles moving along the capillary. The data of [20,[30][31][32] show the behavior S T /a = const.…”
mentioning
confidence: 99%
“…In view of this discrepancy, we complete our discussion of hydrodynamic effects by considering thermophoresis along the boundaries, where confinement is expressed in terms of the ratio of the particle radius a and the width w of the capillary. In view of the experiments [32,33] we consider the perturbative range a w only. In Oseen's model for parallel diffusion, confinement reduces the Stokes-Einstein coefficient of a particle at vertical position z according to D 0 /D = 1 + 9 8 a z + 9 8 a w−z [15].…”
mentioning
confidence: 99%
“…They are based on either equilibrium thermodynamics [4,5,7,10], a hydrodynamic description [11][12][13], or fluctuating hydrodynamics [14], but no microscopic theory is generally accepted [9,15]. These fundamental issues and possible applications motivate a microfluidic interest in thermophoresis [16][17][18][19][20].…”
mentioning
confidence: 99%